Validasi Media Ular Tangga Pada Materi Al-Mumit, Al-Hayyu, Al-Qayyum, dan Al-Ahad Kelas V SD - A'ini, Nova Nur; Majidi, Muhammad Wahid (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The use of interactive learning media is increasingly important in the digital era to increase students' interest in learning. Currently, game-based media is a solution that offers a more enjoyable and in-depth learning experience, so that it can motivate students to understand the subject matter. Although many studies have shown that digital learning media can increase the effectiveness of learning, the use of digital games based on religious material is still limited. Therefore, this study aims to develop and validate learning media in the form of a digital snake and ladder game for Al-Mumit, Al-Hayyu, Al-Qayyum, and Al-Ahad materials for grade V students. The method used is Research and Development (R&D) with a 4D approach (Define, Design, Develop, Disseminate), but this study is limited to the development stage. The results of the study showed that the validation of the material obtained a score of 83.4%, which is included in the